Sclerosing stromal tumor of the ovary: A case report - Navjot Kaur; Neelam Sharma; Vijay Kaushal; Sarita Asotra; Jagjit Singh Chahal (Archives of Medicine and Health Sciences, 2014)
Sclerosing stromal tumors are benign ovarian neoplasms of the sex cord-stromal category, occurring predominantly in the second and third decades of life. Herein, we report a 23-year-old female who presented with pelvic pain, irregular menses but normal hormonal status and was diagnosed as having a right ovarian tumor. A right oophorectomy was performed, and microscopic examination revealed a sclerosing stromal tumor of the right ovary. We stress the importance of being familiar with sclerosing stromal tumors when evaluating ovarian neoplasms in young women, in order to contribute to the appropriate clinical management, preventing extensive and unnecessary surgery, and preserving fertility.